واقع العملات الافتراضية - الشيخي أميمة نجيب (Scientific Journal of University of Benghazi, 2021)
The study aims to research the reality of virtual currencies by introducing virtual currencies, their most important types and their advantages. Additionally, the study aims to highlight the most important risks arising from dealing with virtual currencies and to clarify the concept of blockchain technology and its role in protecting the user of virtual currencies. The study concluded that virtual currencies are electronic numbers that do not have a physical presence and are obtained through mining or buying from financial sites or stock exchanges. The study also found that virtual currencies face a range of over lapping risks due to the absence of an official body to issue them. To protect customers from forgery and manipulation, virtual currencies use blockchain technology.